Alternate Atlantic forest and climate phases during the early Pleistocene 41 kyr cycles in southeastern Brazil. (15th June 2022) - Rodríguez-Zorro, Paula A.; Ledru, Marie-Pierre; Favier, Charly; Bard, Edouard; Bicudo, Denise C.; Garcia, Marta; Marquardt, Gisele; Rostek, Frauke; Sawakuchi, André O.; Simon, Quentin; Tachikawa, Kazuyo
Abstract: The early Pleistocene was driven by 41 kyr glacial cycles that have been rarely characterized in continental records, especially in South America. Most of long-term records derive from marine records ( e.g. sea surface temperatures (SST)) and have been widely used to infer past climate dynamics but implications for the continent have rarely been evaluated. We present an early Pleistocene record (COL17c) from the Colônia basin in the Atlantic forest domain in southeastern Brazil. Our aim was to integrate past environmental dynamics and the drivers of change between ca. 1.5 to 1.3 Myr at the latitude of Colônia (23°S; ca. 700 m a.s.l.). We applied a multi-proxy approach including pollen, charcoal, X-Ray fluorescence scanning (XRF), biomarkers and diatoms. We identified three glacial periods and four interglacials containing a continuous cool forest, mainly dominated by Araucaria . The glacial periods were characterized by increases in organic matter input on the lake, semi-deciduous forest, and shore and herbaceous vegetation. In contrast, the interglacials were marked by increases in evergreen forest and reduced organic matter input. We attribute these alternating phases of vegetation and lake productivity to meridional temperature differences that regulated the input of moisture at the latitude of Colônia. After 1.430 Myr, glacial and interglacial periods showed a different dynamism with an increase in Araucaria forests and drops in relative temperature, concomitant with regional long-trend cooling observed in marine records. The observed forest responses inferred from the COL17c record are in phase with regional climate features such as the development of the cold Pacific tongue and the equatorward migration of subpolar fronts, highlighting the strong influence of the Southern Hemisphere at Colônia during the early Pleistocene. Highlights: The Atlantic forest was sensitive to variations in moisture and temperature during the early Pleistocene. During interglacial periods evergreen forests dominated. During glacial periods grassland and semi-deciduous forests expanded. Araucaria forest was continuous during the early Pleistocene with an abrupt change in amplitude at 1.43 Myr. Early Pleistocene cooling influenced Araucaria forest expansion.